ANALISIS PERBANDINGAN METODE LOAD BALANCE PCC DENGAN NTH MENGGUNAKAN MIKROTIK - Adani, Muhammad Faizin; Jusak, Jusak; Pratikno, Heri (Journal of Control and Network Systems (JCONES), 2016)
Load balancing is a technique on the Mikrotik to distribute the traffic load on the connection of two or more lines in a balanced way, so that traffic can run optimally, maximize throughput, minimize response time and avoid overload on one connection line. Load balancing has several methods, of which the PCC and Nth.The first phase of our works devoted to configure the IP addresses for the four routers in the system. Next we configurated the PCC load balance and the Nth load balance separately. On the second phase we transfered of data from client to server and enabled the wireshark to monitor network activities. On the third phase we analyzed throughput, packet loss, and fairness index obtained from the wireshark.Based on the research results, it is shown that using the throughput test parameter the PCC utilize the resource of the network (bandwidth) mostly in one line. On the other hand, the Nth works by dividing the resource utilization for both lines equally. In terms of the packet loss, it is indicated that the Nth has greater packet loss than the PCC. For the fairness index parameter, it shows that the Nth index has a larger value of fairness. In other words, Nth can be considered as fairer than PCC.